Predictors of Future Atrial Fibrillation Development in Patients with Hypertrophic Cardiomyopathy: A Prospective Follow‐Up Study. Issue 3 (23rd October 2015) - Tuluce, Kamil; Yakar Tuluce, Selcen; Kahya Eren, Nihan; Kocabas, Ugur; Akyildiz Akcay, Filiz; Gunduz, Ramazan; Akyildiz, Zehra I.; Ergene, Oktay
Abstract : Background: We evaluated whether left atrial (LA) phasic functions, P‐wave dispersion (PWD), and plasma NT‐proBNP levels could predict future development of atrial fibrillation (AF) in patients with hypertrophic cardiomyopathy (HCM). Methods: Seventy patients with HCM were evaluated. The LA phasic functions including the LA total emptying volume (LATEV), LA total emptying fraction (LATEF), LA active emptying volume (LAAEV), LA active emptying fraction (LAAEF), LA passive emptying volume (LAPEV), and LA passive emptying fraction (LAPEF) were evaluated. P‐wave dispersion was calculated. Plasma NT‐proBNP levels were measured on the same day with echocardiographic study. Results: Patients were followed up 53.09 ± 1.87 months. Patients who developed AF (n = 18) had significantly higher PWD values, NT‐proBNP levels, LAVI, E/E' av, and resting LVOT gradients and significantly lower LATEF and LAAEF. In multivariate analysis, LATEF (P = 0.002), LAAEF (P = 0.007), logNT‐proBNP level (P = 0.022), and PWD (P = 0.018) were associated with AF development. The results of receiver operating characteristic analysis revealed that a LATEF cutoff value 49% with 72% sensitivity and 81% specificity, a LAAEF cutoff value of 36% with 72% sensitivity and 71% specificity, and an NT‐proBNP cutoff value of 720 pg/mL predicted future AF development with 72% sensitivity and 60% specificity. A PWD cutoff value of 47.5 msecond predicted future AF development with 78% sensitivity and 72% specificity. Conclusion: In patients with HCM, LA phasic functions, PWD, and NT‐proBNP levels predict future development of AF. Assessment of LA phasic functions during routine echocardiographic evaluation and measuring NT‐proBNP levels and PWD values of patients with HCM during daily practice may provide important data in predicting those at high risk of AF occurrence.